The Influence of Company Size on Energy Management Systems Adoption: A System Dynamics Model - Camila Reis; Lívia Benvenutti; Lucila Campos; Maurício Uriona (BBR: Brazilian Business Review)
Isomorphism can be understood as the process that leads one population to resemble another in the same environmental conditions. Isomorphic pressures are felt differently depending on the size of the organization and can disturb the adoption of Energy Management Systems, such as ISO 50001. Given institutional differences, how can government´s coercive pressures impact the spread of ISO 50001 in each size group? To what extent can they influence the overall spread of certification? This article applies the Bass diffusion model to assess the ISO 50001 certification over the 2016-2040 period, using a system dynamics modeling approach. It proposes an extension of the diffusion model related to market stakeholder pressure, based on institutional theory. The results showed that financial and fiscal incentives provided the most significant impact on the overall number of certified industries. Large companies are the most relevant segment for certification without additional policies, while smaller ones benefit significantly from incentive programs. This study reinforces the relevance that stakeholders have in promoting greener standards and initiatives, and offers useful lessons on the dynamics of adopting energy management systems.